Best Practice No 179: Guidelines for breast needle core biopsy handling and reporting in breast screening assessment. Issue 9 (27th August 2004) - Ellis, I O; Humphreys, S; Michell, M; Pinder, S E; Wells, C A; Zakhour, H D
Abstract : Non-operative diagnosis has become the norm in breast disease assessment and, until relatively recently, fine needle aspiration cytology has been the sampling method of choice. The introduction of automated core biopsy guns in the mid 1990s led to the additional introduction of core biopsy in assessment units. This paper presents a summary of the guidance on handling and routine reporting of breast needle core biopsy specimens in the context of breast disease multidisciplinary assessment. This guidance has been produced by the UK National Coordinating Committee for Breast Screening Pathology and is endorsed by the European Commission working group on breast screening pathology.